IMPLEMENTATION OF DEMONSTRATION PLOTS DME NYAMPLUNG (Calophyllum inophyllum L) IN BULUAGUNG AND PATUTREJO VILLAGES - Bambang Uripno; Lala m. Kolopaking; R. Margono Slamet; Siti Amanah (Chemical Engineering Diponegoro University, 2014)
The purpose of this study were to evaluate the condition of the frist demplot DME nyamplung. Energy self sufficient village program aims to improve stock and diverse energy source and society economic opportunity. Nyamplung is very potential plant to be used as raw material of biofuel, because it has very high fat plant content and has not be used for food. The biofuel from nyamplung is a new innovation. Involvement of forest village community in biofuel industry development both as producers and as consumers is very important. Forestry Ministry has established demonstration plots in Buluagung and Patutrejo villages as a facilitation in developing biofuel nyamplung silvoindustry. Up to now, the demplots still faces some problems. The researh method was qualitatif analysis. Collecting data from 62 respondents using purposive sampling. Data were collected using questionnaires, field obsevation, and in-depth interview. Focus group discussion was used to confirm the data from the respondents. Research results show that the demplots have not been developed through participatory approach. Involvement of community to demplots activity is low. Involvement of the village communities are significantly correlated to biofuel price, technology innovation, role of demplot and support from local leaders.